A history of the aviation industry in Latin America : nationalism, developmentalism and neoliberalism in Chile - Barría Traverso, Diego (Routledge, 2024)
"This book analyzes both the Chilean state policies on commercial aviation and the corporate history of the state-owned ailrine Línea Aérea Nacional (LAN) between 1929 and 1989. The book covers a transition from the early adoption of policies that were nationalist, from both the national security and economic standpoints, through the complete deregulation of the skies and the sale of the state airline to foreign capital. Both processes were implemented by army officers (Carlos Ibáñez del Campo and Augusto Pinochet, respectively). It shows that LAN's corporate development was marked by the construction of a national aviation paradigm that, albeit initially characterized by a clear definition of nationalism with the state as preeminent, was far from static over time. As from 1929, the role of the state airline, as both a transport service provider and an instrument of public policy, was subject to review. This was due in part to Chile's political dynamics in the twentieth century in terms of matters such as the level of consensus/dissent about the development model and the role of the state, SOEs and the private sector in the economy. It also reflected trends in the commercial airline industry globally, technological advances and, as from the 1970s, pressures to liberalize the sector"-- Provided by publisher.
Keywords: Aircraft industry -- Chile -- History.; Aircraft industry -- Government policy -- Chile.; Chile -- Economic policy.; Aeronautics and state -- Chile.; elektronické knihy; electronic books